First Total Synthesis of Cryptopyranmoscatone A3 and Cryptopyranmoscatone B4 - Reddy, A. Maheswara; Sabitha, Gowravaram (SynOpen, 2018)
The first total synthesis of cryptopyranmoscatones A3 and B4 has been accomplished from d-ribose or but-3-ynol. The key steps involved in the synthesis are oxa-Michael addition, highly diastereoselective Brown allylation, and ring closing metathesis (RCM) and cross metathesis (CM) reactions.
Keywords: oxa-Michael addition; Brown asymmetric allylation; ring-closing metathesis; cross metathesis